1998
DOI: 10.1111/j.1574-6941.1998.tb00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and ecology of acidophilic microorganisms

Abstract: Microbial life in extremely low pH (<3) natural and man‐made environments may be considerably diverse. Prokaryotic acidophiles (eubacteria and archaea) have been the focus of much of the research activity in this area, primarily because of the importance of these microorganisms in biotechnology (predominantly the commercial biological processing of metal ores) and in environmental pollution (genesis of ‘acid mine drainage’); however, obligately acidophilic eukaryotes (fungi, yeasts, algae and protozoa) are als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
194
1
5

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 414 publications
(205 citation statements)
references
References 33 publications
5
194
1
5
Order By: Relevance
“…In the laboratory community, increased archaeal stress response proteins correlated with the stress response of Leptospirillum group II. As community production is likely dependent on all microbial species because of mutualistic and synergistic interactions (Hallmann et al, 1992;Johnson, 1998), stress to the archaea may have further decreased net production and growth rates in laboratory reactors.…”
Section: Acid Mine Drainage Chemoautotrophic Productionmentioning
confidence: 99%
“…In the laboratory community, increased archaeal stress response proteins correlated with the stress response of Leptospirillum group II. As community production is likely dependent on all microbial species because of mutualistic and synergistic interactions (Hallmann et al, 1992;Johnson, 1998), stress to the archaea may have further decreased net production and growth rates in laboratory reactors.…”
Section: Acid Mine Drainage Chemoautotrophic Productionmentioning
confidence: 99%
“…Bacterial catalysis is also likely to play an Tebo and He (1999), copyright 2000 American Chemical Society. Recent reviews of the role of microbial activity in the various processes are indicated by the superscripted letters: (a) circumneutral pH: Lovley (2000), Thamdrup (2000); acidic pH: Johnson (1998), Blake and Johnson (2000), see also Küsel et al (1999) and Peine et al (2000) (b) circumneutral pH: direct enzymatic catalysis doubtful; see Thamdrup et al (1993), Lovley (1994), and Schippers and Jørgensen (2001); acidic pH: Blake and Johnson (2000), Pronk and Johnson (1992). (2000); acidic pH: Johnson (1998), Blake and Johnson (2000); see also Edwards et al (2000).…”
Section: Bacterial Fe Redox Cyclingmentioning
confidence: 99%
“…Low complexity, extremophilic consortia that thrive in acid mine drainage (AMD) environments have been proposed as a model system for the study of natural microbial communities (Denef et al, 2010b). Ecological interactions such as competition, mutualism, predation and synergism have been described in such environments (Johnson, 1998). AMD biofilm communities from the Richmond Mine at Iron Mountain, CA, USA have been well characterized using culture independent techniques (Edwards et al, 1999;Bond et al, 2000a, b;Druschel et al, 2004;Wilmes et al, 2008b), and have also been the subject of intensive genomic and proteomic studies (Tyson et al, 2004;Ram et al, 2005;Lo et al, 2007;Simmons et al, 2008;Denef et al, 2009), making them ideal for in-depth ecological analyses.…”
Section: Introductionmentioning
confidence: 99%